L’emplec dels pronoms subjèctes e la lenga d’Augièr Galhard - Patric Sauzet (Lengas)
In the form of Occitan used by Augièr Galhard (1533 ?-1595 ?) subject pronouns occur with a high degree of frequency. Medieval Occitan however can accurately be classified as null subject language and the same is true for more recent forms of the language. The present paper intends to show that this is not (as has been argued) a mere imitation of the French pattern, but rather a reflex of the grammatical evolution of the Occitan language. Specifically it is assumed that loss of morphological case marking in nouns, along with its preservation in pronouns, allowed intensive use of subject pronouns. Later, as case marking also was totally obliterated in pronouns, as reflected by the generalization of the 1stp person singular ieu against former contrastive use of ieu (nominative) vs mi (oblique). Loss of the ieu /mi opposition in favour of ieu in most Occitan speaking areas corresponds to the fixation of a syntactic pattern allowing null subjects (or giving flexion pronominal value). In some northern dialects of Occitan (Naut Limosin, Marchés) as in French, oblique form mi (French moi) has been generalized as a pronominal free form while the nominative form tended to become obligatory and drifted toward flexional status.